Exonic mutations associated with atopic dermatitis disrupt lympho‐epithelial Kazal‐type related inhibitor action and enhance its degradation. Issue 2 (9th September 2019) - Ramesh, Karthik; Matta, Sri Anusha; Chew, Fook Tim; Mok, Yu Keung
Abstract: Background: Skin desquamation is facilitated by serine proteases KLK5 and KLK7, which are tightly regulated by lympho‐epithelial Kazal‐type related inhibitor (LEKTI). LEKTI itself is controlled through degraded by mesotrypsin. Here, we sought to determine whether LEKTI exonic mutations associated with atopic dermatitis (AD) affect the protease inhibitory activity of LEKTI or its susceptibility to mesotrypsin degradation. Methods: The inhibitory activities of the LEKTI domain 4 (D4) and D6 WT and AD‐associated mutants on the enzyme activities of KLK5 and KLK7 were compared using fluorogenic substrates. A keratinocyte cell culture system using HaCat cells was established to assess the role of D6 WT and D386N on triggering inflammation via the induction of thymic stromal lymphopoietin (TSLP). A degradation assay was used to assess the susceptibility of D4 and D6 mutants to mesotrypsin degradation. Results: Enzymatic assays revealed that the D6 D386N mutation affected the inhibitory activity of LEKTI on KLK5 but not KLK7. Other exonic mutations on D6 (N368S, V395M, and E420K) and D4 (R267Q) did not alter LEKTI inhibition. The D386N mutation disrupted the role of D6 in suppressing TSLP induction by KLK5 in HaCat cells. Although WT D4 is more susceptible to mesotrypsin degradation than WT D6, the D4 R267Q mutant was more resistant to mesotrypsin degradation, whereas the D6 E420K mutant showed enhanced mesotrypsin‐mediated degradation. Conclusion: Exonic mutations in D6, which previously have been associated with AD, may cause a disruption of inhibitory activity on KLK5 or enhance the degradation by mesotrypsin. Abstract : KLK5 protease is responsible for skin homeostasis and is under the tight inhibitory control of the multidomain proteinase inhibitor, LEKTI, encoded by SPINK5 . D386N SNP at the active site of LEKTI disrupts its inhibitory activity, whereas E420K SNP enhances its degradation by mesotrypsin. Hyperactive KLK5 cleave PAR2 and activate TSLP leading to Pro‐Th2 innate immune response independent of skin barrier function and environmental factors . KLK5, Kallikrein 5; LEKTI, Lympho‐epithelial Kazaltype‐related inhibitor; NF‐κB, Nuclear factor κB; PAR2, Proteaseactivated receptor 2; SNP, Single nucleotide polymorphism; TSLP, Thymic stromal lymphopoietin; WT, Wild‐type.